Searching for rehabilitation in nonparametric regression models with exogenous treatment assignment - Daniel J. Henderson; Esfandiar Maasoumi (Institute for the Study of Labor (IZA), 2012)
This paper offers some new directions in the analysis of nonparamertric models with exogenous treatment assignment. The nonparametric approach opens the door to the examination of potentially different distributed outcomes. When combined with cross-validation, it also identifies potentially irrelevant variables and linear versus nonlinear effects. Examination of the distribution of effects requires distribution metrics, such as stochastic dominance tests for ranking based on a wide range of criterion functions, including dollar valuations. We can identify subgroups with different treatment outcomes. We offer an empirical demonstration based on the GAIN data. In the case of one covariate (English as the primary language), there is support for a statistical inference of uniform first order dominant treatment effects. We also find several others that indicate second and higher order dominance rankings to a statistical degree of confidence.
Keywords: C14; 330; bootstrap; GAIN; nonparametric; rehabilitation; stochastic dominance; treatment effects; Nichtparametrisches Verfahren; Statistischer Test; Stochastischer Prozess; Theorie; Arbeitsmarktpolitik; Wirkungsanalyse; Kalifornien